A Cone Measure of Noncompactness and Some Generalizations of Darbo's Theorem with Applications to Functional Integral Equations. (18th October 2016) - Jleli, Mohamed; Mursaleen, Mohammad; Sadarangani, Kishin; Samet, Bessem
Abstract : We introduce the concept of cone measure of noncompactness and obtain some generalizations of Darbo's theorem via this new concept. As an application, we establish an existence theorem for a system of integral equations. An example is also provided to illustrate the obtained result.